2022
DOI: 10.1155/2022/5496872
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Thoracoscopic Surgery with the da Vinci Surgical System versus Video-Assisted Thoracoscopic Surgery for Lung Cancer

Abstract: Objective. To assess the clinical efficacy of thoracoscopic surgery with the da Vinci surgical system versus video-assisted thoracoscopic surgery (VATS) for lung cancer. Methods. From August 2019 to December 2020, 193 patients with lung cancer assessed for eligibility scheduled for surgery in our hospital were recruited and assigned at a ratio of 1 : 1 to receive VATS (control group) or thoracoscopic surgery with the da Vinci surgical system (research group). The primary measurement is the clinical efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The popularization of thoracoscopic surgery has reduced surgical traumatic stress, alleviated patients' postoperative pain, decreased the incidence of postoperative complications, and accelerated patients' recovery. However, the destruction of the tissue integrity and the generation of new trauma during surgery are still unavoidable [8]. Ethun et al [9] Am J Transl Res 2024;16 (1):179-189 reported that the incidence of postoperative complications in lung cancer patients was as high as 14.6-18.87%, and the incidence of postoperative complications and adverse reactions in patients with lung cancer combined with coronary artery disease was up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…The popularization of thoracoscopic surgery has reduced surgical traumatic stress, alleviated patients' postoperative pain, decreased the incidence of postoperative complications, and accelerated patients' recovery. However, the destruction of the tissue integrity and the generation of new trauma during surgery are still unavoidable [8]. Ethun et al [9] Am J Transl Res 2024;16 (1):179-189 reported that the incidence of postoperative complications in lung cancer patients was as high as 14.6-18.87%, and the incidence of postoperative complications and adverse reactions in patients with lung cancer combined with coronary artery disease was up to 50%.…”
Section: Introductionmentioning
confidence: 99%